UANG BELANJA (UANG PANAIK) DALAM PERKAWINAN SUKU BUGIS PADA MASYARAKAT RETEH KABUPATEN INDRAGIRI HILIR - Andi Aminah Riski; Ridwan Melay; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Uang Panaik is the amount of money the proposal will be met or paid by the male to the female before stepping into mating. Uang Panaik is money that is fairly customary mandatory with the amount agreed to by both parties when the bride's family wants a wedding. Mating systems of indigenous Bugis and is known as one of the mating system is complex because it has a series of processions are very long and the conditions are very strict, is not out of shame culture prevailing in the Bugis called Culture Siri' (shame or feel the price self-humiliation). Uang Panaik also will be more severe when the bride's family requested Sompa (immovable property such as fields and gardens), Erang-erang (accessories wedding reception). Panaik payment can be done at the time of application have been received or the determination of the marriage or at the time of your spending appanaik (day provide spending money), or at the time of the marriage ceremony will take place. Those that make the payment at once and nobody did and completed partial payment at the time of the marriage ceremony will take place. Tribe Bugis from South Sulawesi is known as nomads, until the country came to wilt, especially in Indragiri Hilir Riau Reteh. Bugis community mores adherents are very powerful and even more firmly in the public position up to now, especially in a marriage ceremony, called Mappabotting with Uang Panaik requirements originally requested. Key words: Money Shopping (Uang Panaik), the Marriage of the Bugis, Indragiri Hilir Reteh Society.